KUALITAS TANAH, AIR TANAH, DAN VEGETASI PADA LAHAN REKLAMASI PANTAI MUTIARA, JAKARTA UTARA - Rusdiyanto, Edi; Pratomo, Hurip (LPPM Universitas Terbuka, 2007)
The development of reclamation land of Mutiara Coast for settlement could impact to environment especially soil, groundwater, and organisms. The aim of this study is to examine soil and water qualities which were observed from physical and chemical properties, plants and birds varieties in the reclamation land of Mutiara Coast, North Jakarta. Soil sample is taken in 0-30 cm deep. Groundwater is taken in artessian well which has been built by the developer. Plants specimens is reconded and taken for further identification. All of those data have been analyzed descriptively. The results show that average of physical and chemical of soil parameter vary, on the other hand condition of groundwater in the reclamation land of Mutiara coast is not qualified as clean water. Plants varieties based on Simpson index is relatively low (C=0.1072), and also birds varieties (C=0.521). It was only 4 species found in those area.